O-GlcNAcylation, an Epigenetic Mark. Focus on the Histone Code, TET Family Proteins, and Polycomb Group Proteins - Dehennaut, Vanessa; Leprince, Dominique; Lefebvre, Tony (Frontiers in Endocrinology, 2014)
There are increasing evidences that dietary components and metabolic disorders affect gene expression through epigenetic mechanisms. These observations support the notion that epigenetic reprogramming-linked nutrition is connected to the etiology of metabolic diseases and cancer. During the last five years, accumulating data revealed that the nutrient-sensing O-GlcNAc glycosylation (O-GlcNAcylation) may be pivotal in the modulation of chromatin remodeling and in the regulation of gene expression by being part of the “histone code”, and by identifying OGT (O-GlcNAc transferase) as an interacting partner of the TET family proteins of DNA hydroxylases and as a member of the Polycomb group (PcG) proteins. Thus, it is suggested that O-GlcNAcylation is a post-translational modification that links nutrition to epigenetic. This review summarizes recent findings about the interplay between O-GlcNAcylation and the epigenome and enlightens the contribution of the glycosylation to epigenetic reprogramming.